Remote Gas Pressure Sensor Based on Fiber Ring Laser Embedded With Fabry–Pérot Interferometer and Sagnac Loop - Jia Shi; Yuye Wang; Degang Xu; Yixin He; Junfeng Jiang; Wei Xu; Haiwei Zhang; Genghua Su; Chao Yan; Dexian Yan; Ying Lu; Jianquan Yao (IEEE Photonics Journal, 2016)
In this paper, we propose a remote gas pressure sensor based on a fiber ring laser embedded with a Fabry–Pérot (F–P) interferometer and a Sagnac loop. A compact optic-fiber F–P interferometer is inserted in the fiber laser and works as the sensing head for gas pressure detection. A wavelength selective filter based on optic-fiber Sagnac loop is used in the fiber laser. The sensitivity of −9.69 nm/kPa is obtained with a narrow 3-dB bandwidth less than 0.02 nm and high signal-to-noise ratio (SNR) ∼45 dB. Moreover, the excellent performance of the gas pressure sensor for remote detection is demonstrated.